Ecological Constraints on the Evolution of Consumer Functional Responses - Amarasekare, Priyanga (Frontiers in Ecology and Evolution, 2022)
Intrinsically generated oscillations are a defining feature of consumer-resource interactions. They can have important consequences for the evolution of consumer functional responses. Functional response traits that can maximize resource (consumer) fitness —low (high) attack rates and long (short) handling times — generate high-amplitude oscillations that can predispose species to extinction during periods of low abundances. This suggests that the ecological consequences of consumer-resource oscillations may impede evolutionary outcomes that maximize fitness. Data suggest this to be a strong possibility. Time series analyses reveal consumer-resource cycles to be infrequent in real communities, and functional response studies show a preponderance of low attack rates and/or short handling times that preclude oscillations but maximize neither species' fitness. Here I present an eco-evolutionary model to address this tension between ecological dynamics and the evolution of functional response traits. I show that the empirically observed attack rate-handling time distributions emerge naturally from the interplay between individual-level selection and the population-level constraint of oscillation-induced extinction. Extinction at low abundances curtails stabilizing selection towards trait values that maximize fitness but induce large-amplitude oscillations. As a result, persistent interactions are those with low attack rates and/or short handling times. This finding suggests that differential persistence of genotypes with different attack rate - handling time combinations may act as an ecological constraint on the evolution of consumer functional responses. It emphasizes the importance of incorporating oscillation-induced extinction into models that link food web topology to community persistence.